Performance trade-offs in elite swimmers - Vilain, M.; Careau, V. (Adaptive Human Behavior and Physiology, 2022)
Objectives: Our objective was to study performance trade-offs in elite athletes competing in a multi-event sport requiring a combination of aptitudes that might conflict each other. Swimmers competing in the individual medley, in particular, might face trade-offs as they have to swim (in this specific order) a quarter of the distance in butterfly, backstroke, breaststroke, and freestyle within a single race. Methods: We applied multivariate mixed models to analyse 28 years (1991-2019) of publicly available data on men (N = 121) and women (N = 131) swimmers competing for the 200 m individual medley in the semi-final and final rounds of Olympics and world championships. Results: At the among-individual level, performance in the backstroke and breaststroke were negatively correlated in both men (rind = -0.264 ± 0.126) and women (rind = -0.453 ± 0.103). At the within-individual level, there was a negative correlation between performance in the first and final 50 m of the race in men (re = -0.181 ± 0.055), but not in women (re = 0.001 ± 0.058). Conclusions: To our knowledge, this is the first demonstration of a trade-off between backstroke and breaststroke swimming styles. Such a trade-off might be caused by various extrinsic (e.g., allocation of training time across the four strokes) and intrinsic (e.g., body morphology and muscle physiology) constraints on human performance. The difference in the pattern of within-individual correlations between men and women aligns with pacing strategies described in the literature. Further research is required to better understand the nature of the trade-offs detected here, which could potentially help improving training strategies for the "generalist" individual medley swimmer.